Anesthetic challenge in removing foreign body mimicking cancer in bronchus from a child - Wagle, Bhawana; Regmi, Yogesh (Nepalese Journal of Cancer, 2017)
We describe a case of 12 years old boy who had recurrent pneumonia for 1 year, under investigation for bronchogenic malignancy. He was found to have foreign body in his bronchus, that was successfully removed with a 11 mm gastroscope.